Carbon nanostructures supported on Co/serpentinite for sulfentrazone removal - Diogo, Emilay Baessa Teixeira; Vieira, Angelica Fonseca Pinto; Nascimento, Mayra Aparecida; Pinto, Paula Sevenini; de Paula, Fabiano Gomes Ferreira; Moreira, Renata Pereira Lopes; Teixeira, Ana Paula de Carvalho (Frontiers in Carbon, 2024)
In this work, the serpentinite rock was impregnated with cobalt, 5, 10 and 20% and used as a support for the synthesis of carbon nanostructures by CVD (chemical vapour deposition) process, at 900 o C. This temperature was chosen due to the high thermal stability of the carbon source. The materials were characterized by X-ray diffraction, Raman spectroscopy, thermal analysis, scanning and transmission microscopy. As expect the main phases formed were forsterite, Mg2SiO4, graphitic carbon and metallic cobalt. All the synthesis showed the formation of carbon structures as multiwalled carbon nanostructures over cobalt cores. The carbon structures showed good thermal stability, between 470 and 600 o C. The higher the cobalt content, the higher the yield of the carbon structures synthesis, i.e. 14, 23 and 37% for Serp5, Serp10 and Serp20, respectively. The produced materials were used to removal of the environmental contaminant sulfentrazone. After CVD process, the removal of sulfentrazone increase to 17.3, 18.4 and 25.2% for Serp5, Serp10 and Serp20, respectively, showing an increase in sulfentrazone removal with the increase in carbon content. In addition, the percentage of sulfentrazone removal by Serp20 was greater at acidic pH values, decreasing from 41.7 to 12.7% with an increase from 2 to 10 in pH. The removal capacity obtained experimentally at a sulfentrazone concentration of 50 mg L -1 was equal to 14.9 mg.g -1 . According to literature and data obtained in this work, it was observed that the removal of contaminants from the aqueous medium occured through two mechanisms: reduction of the organic compound by Co nanoparticles and adsorption carried out by carbon nanostructures.